2007
DOI: 10.1210/jc.2006-2135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methimazole and Propylthiouracil in Patients with Hyperthyroidism Caused by Graves’ Disease

Abstract: MMI 15 mg/d is suitable for mild and moderate GD, whereas MMI 30 mg/d is advisable for severe cases. PTU is not recommended for initial use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
2
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(173 citation statements)
references
References 14 publications
5
160
2
6
Order By: Relevance
“…This study also showed that the incidence of adverse effects in patients treated with MMI was significantly lower than in those treated with PTU [25]. Based on these findings, the JTA guidelines recommend MMI as the first-choice ATD for the treatment of compensated Graves' disease, except during early pregnancy [26].…”
Section: ■ Recommendationmentioning
confidence: 74%
“…This study also showed that the incidence of adverse effects in patients treated with MMI was significantly lower than in those treated with PTU [25]. Based on these findings, the JTA guidelines recommend MMI as the first-choice ATD for the treatment of compensated Graves' disease, except during early pregnancy [26].…”
Section: ■ Recommendationmentioning
confidence: 74%
“…This will be women who started ATD therapy recently (<6 months), who still have suppressed TSH, who have a relatively high serum T 3 (76), high levels of TRAb, large goitre, active orbitopathy, or other signs of active disease. In such women, MMI/CMZ should be replaced with PTU in early pregnancy (preferably in gestational week 5), using a dose ratio of 1:20 (77,78,79), e.g. 200 mg PTU per day replaces 10 mg MMI (or 15 mg CMZ).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…The JTA reported that MMI 15 mg/d is suitable for mild and moderate Graves' disease, whereas MMI 30 mg/d is advisable for severe cases. Propylthiouracil is not recommended for initial use because of high frequency of side effects (5).…”
Section: Nobuyuki Aminomentioning
confidence: 99%